Relationship between Academic Perfectionism and Depression: Role of Self Concealment among Students - Salma Malik, Saba Ghayas, Shaista Khalid (PJE, 2023)
The mediational role of self-concealment in relationship with Academic Perfectionism and Depression is explored in the present study. A sample of students (N=200) was taken from various departments of the University of Sargodha using a purposive sampling technique. Self- concealment, academic perfectionism and depression were measured by using Urdu translated Self-Concealment Scale (SCS; Malik & Ghayas, 2014) Academic Perfectionism Scale (APS; Malik & Ghayas, 2014) and Urdu translated depression subscale of DASS (Farooqi & Habib, 2010) respectively. Results indicated the academic perfectionism as a significant positive predictor of self-concealment and depression. Furthermore, data analysis revealed that self-concealment was a significant positive predictor of depression among university students. The results of this study also indicated that self-concealment also plays the role of a mediator in the relationship between perfectionism and depression. Non-significant gender differences were found in depression among university students. Moreover, the current study yielded that the level of self-concealment was higher among males than females, whereas the level of academic perfectionism was higher among females as compared to males.